2000
DOI: 10.1093/gerona/55.11.m684
|View full text |Cite
|
Sign up to set email alerts
|

Height, Weight, and Body Mass Index of Elderly Persons in Taiwan

Abstract: The comparison indicates cross-cultural differences existing in the prevalence of obesity, which may be due to aging, nutritional status, or environmental factors. For future research, the relationship of anthropometric data to socioeconomic status and behavioral factors will be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 14 publications
7
31
0
Order By: Relevance
“…Using regression analyses and the ROC plots to study the relationships between BMI and DEXA-derived PBF, we have shown that the BMI cutoff point for obesity for our local healthy men and women aged 30-70 years was 27 and 25 kg/m 2 , respectively, concurring with earlier suggestions by many Asian investigators (6,8,10,11,30,32,33). Where we differ from these earlier studies is in the finding of a clear gender difference in BMI cutoff for obesity for Asian men (27 kg/m 2 ) and women (25 kg/m 2 ); therefore, this gender difference must be taken into consideration when BMI is used as an index of obesity for Asian populations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using regression analyses and the ROC plots to study the relationships between BMI and DEXA-derived PBF, we have shown that the BMI cutoff point for obesity for our local healthy men and women aged 30-70 years was 27 and 25 kg/m 2 , respectively, concurring with earlier suggestions by many Asian investigators (6,8,10,11,30,32,33). Where we differ from these earlier studies is in the finding of a clear gender difference in BMI cutoff for obesity for Asian men (27 kg/m 2 ) and women (25 kg/m 2 ); therefore, this gender difference must be taken into consideration when BMI is used as an index of obesity for Asian populations.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have shown that the BMI cutoff points for the prescribed classifications as overweight and obese differed from those recommended by WHO. For some Asian populations, including those from Taiwan, Hong Kong, and Singapore, and also a Spanish population, the corresponding BMI cutoff points for overweight and obese were 23 kg/m 2 and 25-27 kg/m 2 , respectively (6,8,10,11,(30)(31)(32)(33). Hence, there was a need to review the WHO-recommended cutoff limits for obesity in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, in which a division was made into 6 groups, confirms the earlier studies [13,14,15]. In persons above 70 years of age, dwindling values of skinfold thickness are observed.…”
Section: Discussionsupporting
confidence: 91%
“…Namely, the conclusion is that with age the tendency of body mass increase appears, the same refers to the percentage increase of the fat tissue and BMI as well as the decrease of muscle mass. At the same time, the same worldwide studies show that during the late elderly age the increase of body mass and the fat tissue level are inhibited or even diminished [26,27]. This is also confirmed by the study conducted by our team.…”
Section: Discussionsupporting
confidence: 88%